The temperature-dependent decomposition of SiO studied by infrared vibrational spectroscopy - Wetzel, Steffen; Klevenz, Markus; Pucci, Annemarie; Gail, Hans-Peter (Applied spectroscopy, 2012)
The temperature dependence of vibrational bands in SiO films deposited onto Si was studied under ultra high vacuum conditions. In the first series of measurements, films were deposited at various substrate temperatures from 40 K to 573 K and infrared spectra were monitored in situ between 450 cm−1 and 5000 cm−1. In a second series of measurements, a film was deposited at 300 K and post-annealed to various temperatures ranging from 373 K to 1173 K. A shift of the strongest vibrational frequency of SiO by several 10 cm−1 to higher wavenumbers with increasing temperature was observed in both kinds of experiments. The observed spectral shifts are considered as an indication of changes in the frequency of occurrence of the various Si-SiyO4-y units (0 ⩽ y ⩽ 4).
Gesehen am 23.04.2018